Identification of Bacillus Strains for Biological Control of Catfish Pathogens - Ran, Chao; Carrias, Abel; Williams, Malachi A.; Capps, Nancy; Dan, Bui C. T.; Newton, Joseph C.; Kloepper, Joseph W.; Ooi, Ei L.; Browdy, Craig L.; Terhune, Jeffery S.; Liles, Mark R. (PloS one, 2012)
Bacillus strains isolated from soil or channel catfish intestine were screened for their antagonism against Edwardsiella ictaluri and Aeromonas hydrophila, the causative agents of enteric septicemia of catfish (ESC) and motile aeromonad septicaemia (MAS), respectively. Twenty one strains were selected and their antagonistic activity against other aquatic pathogens was also tested. Each of the top 21 strains expressed antagonistic activity against multiple aquatic bacterial pathogens including Edwardsiella tarda, Streptococcus iniae, Yersinia ruckeri, Flavobacterium columnare, and/or the oomycete Saprolegnia ferax. Survival of the 21 Bacillus strains in the intestine of catfish was determined as Bacillus CFU/g of intestinal tissue of catfish after feeding Bacillus spore-supplemented feed for seven days followed by normal feed for three days. Five Bacillus strains that showed good antimicrobial activity and intestinal survival were incorporated into feed in spore form at a dose of 8×10(7) CFU/g and fed to channel catfish for 14 days before they were challenged by E. ictaluri in replicate. Two Bacillus subtilis strains conferred significant benefit in reducing catfish mortality (P<0.05). A similar challenge experiment conducted in Vietnam with four of the five Bacillus strains also showed protective effects against E. ictaluri in striped catfish. Safety of the four strains exhibiting the strongest biological control in vivo was also investigated in terms of whether the strains contain plasmids or express resistance to clinically important antibiotics. The Bacillus strains identified from this study have good potential to mediate disease control as probiotic feed additives for catfish aquaculture.